2014
DOI: 10.5935/1678-9741.20140004
|View full text |Cite
|
Sign up to set email alerts
|

EuroSCORE II and the importance of a local model, InsCor and the future SP-SCORE

Abstract: Rev Bras Cir Cardiovasc | Braz J Cardiovasc SurgRev Bras Cir Cardiovasc 2014;29(1) power of discrimination. Still, we must not forget that "few variables as possible" prevails in a model in order to have a greater acceptance [12,13]. At the Heart Institute, Clinics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
2
22
0
2
Order By: Relevance
“…Lisboa et al [5] analyzed the performance of EuroSCORE II in 1000 patients undergoing cardiac surgery, comparing it to the InsCor and EuroSCORE. The authors concluded that only the last two were adequate in all stages of validation, due to mistakes in the design of EuroSCORE II, hence reinforcing the importance of a national risk score model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lisboa et al [5] analyzed the performance of EuroSCORE II in 1000 patients undergoing cardiac surgery, comparing it to the InsCor and EuroSCORE. The authors concluded that only the last two were adequate in all stages of validation, due to mistakes in the design of EuroSCORE II, hence reinforcing the importance of a national risk score model.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, development and validation of local models are becoming increasingly necessary due to demographic, socioeconomic, and cultural aspects of different populations [4,5] . The combination of the data resulting from the risk score models allows for adaptation, improvement and even innovation in treatment programs [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the first validation of the EuroSCORE II was performed by Lisboa et al. [ 15 ] , from the analysis of 1000 consecutive patients undergoing coronary and/or valve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…EuroSCORE II [ 8 ] mortality estimate was 3.48±3.99% and our actual mortality was 8.16%. At a concomitant period, from October 2008 to July 2009, Lisboa et al [ 22 ] demonstrated inadequate calibration of EuroSCORE II at InCOR-FMUSP, and found better calibration of additive and logistic EuroSCORE and InsCor, a locally developed risk model. Indeed, the poorly calibrated EuroSCORE II to predict mortality in the group of patients evaluated reinforces the need for implementation, and widespread use of a Brazilian risk model.…”
Section: Discussionmentioning
confidence: 99%